Analysis of The Effect of Funding Strategy on The Company's Financial Performance at PT Jasamarga Related Business - Ria Marlinda Paallo; Eka Pria Anas (Syntax Corporation, 2022)
Business development is the key to ensure the sustainability of a company. The need for funding to support this development makes the company try to obtain a funding strategy that is in accordance with financial performance. Each investment and risk scheme selected will have an impact on the selection of a funding strategy, this is a case study in research to show the effect of the selected funding strategy on financial performance so that companies obtain appropriate alternative funding strategies. This case study uses an in-depth analysis of financial aspects, sensitivity and simulations conducted at PT Jasamarga Related Business. Based on studies conducted, the funding strategy is a priority requirement for the company in developing the company's business strategy. Financial performance is a reflection of the company's sustainability so that all strategy makers, especially the selection of funding strategies, need to be studied more deeply.